High-flexibility energy storage cable and preparation method thereof
The flame retardant modifier formed by composite of magnesium-aluminum double hydroxide, boron nitride nanosheets and nano-sea carbon black is evenly dispersed in the energy storage cable, solving the problems of reduced thermal conductivity and flexibility of energy storage cables, and improving the Flame retardant properties and thermal conductivity reduce the risk of thermal oxygen aging.
Patent Information
- Application Number
- CN202411814632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The thermal conductivity of existing energy storage cables is reduced under high-filled flame retardant, and flexibility is reduced, which is prone to thermal oxygen aging, resulting in safety hazards.
The flame retardant modifier is formed by combining magnesium-aluminum dihydroxide, boron nitride nanosheets and nano-sea carbon black. The compatibility with rubber is improved through 3-allylrotannin, so that it is evenly dispersed in the energy storage cable. In the rubber protective layer, the filler composite amount is reduced and the thermal conductivity is improved.
It improves the flame retardant performance and thermal conductivity of energy storage cables, reduces heat accumulation, enhances the flexibility and anti-aging ability of the rubber protective layer, and avoids the occurrence of thermal oxygen aging effects.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable materials, and specifically relates to a high-flexibility energy storage cable and a preparation method thereof. Background Art
[0002] As an important type of polymer material, rubber is widely used in the field of protective layers of cable insulation materials. The protective materials of energy storage cables require high flame retardant properties. However, since the rubber molecular chain contains a large number of isolated carbon-carbon double bonds and active allylic hydrogen structures, rubber materials are extremely prone to aging under heat, oxygen, light, ozone and stress conditions. Since the energy storage standard requires that the material meet the thermal life requirement of 125℃×20000h, and is limited by the small space of the energy storage control cabinet, the energy storage cable needs to be bent and folded. If the bending angle is too large, the thermal effect of the rubber material at the bend will be enhanced. If the thermal conductivity of the energy storage cable is insufficient, thermal oxidation aging is likely to occur, leading to cracking, posing a safety hazard.
[0003] Patent CN117612764A discloses an energy storage cable and a preparation method thereof. Rare earth nanomaterials are added to the raw materials for preparing the insulating layer to increase the crosslinking density of the silicone rubber material and the stability between the molecular chains, thereby improving the comprehensive performance and aging resistance of the rubber. However, this solution only uses hydroxy silicone oil as a structure control agent to promote the dispersion of nanomaterials and silica, and has limited improvement on the dispersion of nanomaterials and silica that are easy to agglomerate. In addition, the high filling of fillers causes frictional heat to be generated during extrusion of the rubber, resulting in excessive crosslinking of the rubber and a decrease in thermal conductivity. In addition, the high filling of fillers will also reduce the flexibility of the rubber.
[0004] Patent CN116978607A discloses a rubber manufacturing process for flexible cables, which improves the insulation and heat resistance of the cable by adding ceramic nanofibers to the inner layer made of natural rubber, and improves the strength of the cable rubber and the ability of the rubber to resist cracking when the cable is bent by adding a skeleton layer to the cable structure; however, the natural rubber inner layer in this solution is also limited by the dispersibility of ceramic nanofibers, and the addition of cord fabric in the skeleton layer reduces the thermal conductivity of the skeleton layer. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that excessive addition of flame retardant in flexible energy storage cables leads to reduced thermal conductivity, and to provide a highly flexible energy storage cable and a preparation method thereof.
[0006] The present invention forms a flame retardant modifier by compounding magnesium aluminum double hydroxide, boron nitride nanosheets and nano-white carbon black, and utilizes the compatibility of 3-allyl rhodanine in rubber to uniformly disperse the flame retardant modifier in the rubber protective layer of the energy storage cable, thereby improving the flame retardant effect, reducing the compounding amount of fillers, and improving thermal conductivity.
[0007] The purpose of the present invention can be achieved by the following technical solutions: A highly flexible energy storage cable, comprising the following raw material components by weight: 20-30 parts of flame retardant modifier, 40-50 parts of natural rubber, 10-15 parts of silicone rubber, 2-3 parts of antioxidant, 3-5 parts of tackifying resin, 3-5 parts of vulcanizing agent and 2-3 parts of vulcanization accelerator.
[0008] A method for preparing a highly flexible energy storage cable comprises the following steps: Step 1, in a reaction kettle, disperse nano-silica in anhydrous ethanol by ultrasonic, add 3-chloropropyltriethoxysilane, heat to 45-55°C, stir for 24-36h, filter, wash the precipitate with anhydrous methanol and anhydrous ethanol respectively, and vacuum dry to constant weight to obtain modified nano-silica, disperse the modified nano-silica in anhydrous ethanol in a reaction kettle, add sodium hydroxide to adjust the pH value to 9-10, add modified magnesium aluminum double hydroxide, heat to 45-55°C under a nitrogen atmosphere, stir and react for 24-30h, filter and wash after cooling, and vacuum dry to obtain modified silica hydroxide; Step 2: In a reaction kettle, disperse the modified hydroxide of white carbon black in anhydrous ethanol, disperse the modified boron nitride in anhydrous methanol, add sodium hydroxide to adjust the pH value to 9-10, add them into the reaction kettle under stirring, heat to 60-70° C. under nitrogen protection, stir and react for 3-4 hours, filter, wash with anhydrous ethanol and deionized water, and then vacuum dry at 50-60° C. for 4-6 hours to obtain a flame retardant modifier; Step three, extrude the flame retardant modifier, natural rubber, silicone rubber, antioxidant, tackifying resin, vulcanizer and vulcanization accelerator through a twin-screw extruder and granulate to obtain a flexible energy storage cable material, and use the flexible energy storage cable material as a protective sheath granulate and a conductor and a conductor shielding layer through a non-cross-linked three-layer co-extrusion method to obtain a highly flexible energy storage cable.
[0009] Furthermore, in step one, the usage ratio of nano-silica, anhydrous ethanol and 3-chloropropyltriethoxysilane is 5-8g:300-350mL:15-20g; the usage ratio of the modified nano-silica, anhydrous ethanol and modified magnesium aluminum double hydroxide is 5-8g:300-350mL:40-50g.
[0010] Furthermore, in step 2, the usage ratio of white carbon black modified hydroxide, anhydrous ethanol, modified boron nitride and anhydrous methanol is 45-55g:300-350mL:10-15g:100-150mL.
[0011] Further, the modified magnesium aluminum double hydroxide is prepared by the following steps: 2-Mercaptobenzimidazole is dissolved in 1M sodium hydroxide solution, zinc aluminum layered hydroxide is added, ultrasonic dispersion is carried out, and then stirring is carried out for 24-36 hours. The precipitate is collected by centrifugation, washed with deionized water and anhydrous ethanol, and then vacuum dried to obtain modified magnesium aluminum double hydroxide.
[0012] Furthermore, the usage ratio of 2-mercaptobenzimidazole, sodium hydroxide solution and zinc aluminum layered hydroxide is 70-75 g: 400-500 mL: 40-50 g.
[0013] Further, the zinc-aluminum layered hydroxide is prepared by the following steps: Under nitrogen flow, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in deionized water without carbon dioxide to obtain a salt solution, and the salt solution is added dropwise to a 1.5M sodium nitrite solution in a reaction kettle within 1.5-2 hours, and magnetic stirring is performed during the dropping process. 2M sodium hydroxide solution is continuously added to the reaction kettle during the dropping process to make the pH value of the solution 9.5-10.5, and the temperature is raised to 60-70°C for reaction for 24-36 hours. After cooling, the mixture is centrifuged, washed, and vacuum dried to obtain magnesium aluminum double hydroxide.
[0014] Furthermore, the usage ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, deionized water and sodium nitrite solution is 50-65 g: 30-45 g: 250-300 mL: 500-600 mL.
[0015] Furthermore, the modified boron nitride in step 2 is prepared by the following steps: In a reaction kettle, the boron nitride nanosheet powder is ultrasonically dispersed in a 5M sodium hydroxide solution, heated to 100-120°C for reaction for 24-36 hours, cooled, centrifuged, washed with deionized water, and dried to obtain pretreated boron nitride, the pretreated boron nitride is ultrasonically dispersed in deionized water, ferric chloride is added, and stirred for 12-16 hours, and then 3-allyl rhodanine is stirred and dissolved in hot water at 90-95°C, added to the reaction kettle while stirring, stirred for reaction for 12-16 hours, cooled, filtered, the precipitate is washed with ethanol, vacuum dried at 50-60°C for 4-6 hours, and ground and sieved to obtain modified boron nitride.
[0016] Furthermore, the dosage ratio of pretreated boron nitride, deionized water, ferric chloride, 3-allyl rhodanine and hot water is 10-15 g: 3-4 L: 8-10 g: 10-12 g: 1-1.2 L.
[0017] Furthermore, the antioxidant is N-(4-anilinophenyl)maleimide.
[0018] Furthermore, the tackifying resin is one of solid coumarone resin, liquid coumarone resin and liquid nitrile rubber.
[0019] Furthermore, the vulcanizing agent is sulfur.
[0020] Furthermore, the vulcanization accelerator is one of accelerator NA-22, accelerator D, accelerator CZ, accelerator NOBS, accelerator DM, accelerator M, accelerator TMTD, and accelerator TRA.
[0021] Beneficial effects of the present invention: The high-flexibility energy storage cable prepared by the present invention improves the flame retardant performance of the energy storage cable by compounding the flame retardant to form a flame retardant modifier which is evenly dispersed in the rubber protective layer of the energy storage cable. At the same time, the high thermal conductivity of the flame retardant modifier greatly improves the thermal conductivity of the energy storage cable, reduces the heat accumulation of the energy storage cable, reduces the degree of thermal oxidation aging effect, and the evenly dispersed flame retardant modifier can reduce the filling amount of filler and flame retardant, thereby improving the flexibility of the energy storage cable, so that the rubber protective layer of the energy storage cable has a good degree of cross-linking during vulcanization, and reduces the occurrence of pre-cross-linking.
[0022] The preparation method of the present invention comprises the following steps: coating a boron nitride nanosheet with 3-allyl rhodanine and then grafting the boron nitride nanosheet with 2-mercaptobenzimidazole via a click reaction, utilizing the good compatibility between 3-allyl rhodanine and rubber to improve the compatibility between the flame retardant modifier and the rubber, thereby increasing the dispersion of the flame retardant modifier in the rubber.
[0023] The preparation method of the present invention grafts 2-mercaptobenzimidazole into magnesium aluminum double hydroxide by ion replacement method, reacts with chlorine groups on the surface of white carbon black modified by a coupling agent, and uniformly grafts white carbon black into the magnesium aluminum double hydroxide to form a composite flame retardant, thereby improving the dispersibility and synergistic effect of the flame retardant and enhancing the flame retardant effect. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1: A highly flexible energy storage cable and a preparation method thereof, comprising the following steps: Step 1: Under nitrogen, 50 g of magnesium nitrate hexahydrate and 30 g of aluminum nitrate nonahydrate are dissolved in 250 mL of deionized water without carbon dioxide to obtain a salt solution. The salt solution is added dropwise to 500 mL of 1.5 M sodium nitrite solution in a reactor within 1.5 hours. The dropping process is magnetically stirred. During the dropping process, 2 M sodium hydroxide solution is continuously added to the reactor to make the solution pH value 9.5. The temperature is raised to 60° C. to react for 24 hours. After cooling, the precipitate is collected by centrifugation, and the precipitate is washed with 100° C. deionized water and anhydrous ethanol in turn, and vacuum dried at 55° C. for 24 hours to obtain magnesium aluminum double hydroxide.
[0026] Step 2: Dissolve 70 g of 2-mercaptobenzimidazole in 400 mL of 1 M sodium hydroxide solution, add 40 g of zinc aluminum layered hydroxide, disperse by ultrasonication, and then stir to react for 24 h. Collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol, and dry it in vacuum at 55 ° C for 12 h to obtain modified magnesium aluminum double hydroxide.
[0027] Step 3: In a reactor, ultrasonically disperse 5 g of nano-silica in 300 mL of anhydrous ethanol, add 15 g of 3-chloropropyltriethoxysilane, heat to 45 ° C and stir for 24 h, filter and wash the precipitate with anhydrous methanol and anhydrous ethanol respectively, and vacuum dry at 45 ° C to constant weight to obtain modified nano-silica. In a reactor, disperse 5 g of modified nano-silica in 300 mL of anhydrous ethanol, add sodium hydroxide to adjust the pH value to 9, add 40 g of modified magnesium aluminum double hydroxide, heat to 45 ° C under a nitrogen atmosphere, stir and react for 24 h, filter after cooling, wash with anhydrous toluene, anhydrous ethanol and deionized water in turn, and vacuum dry at 45 ° C to obtain modified silica hydroxide.
[0028] Step 4: ultrasonically disperse the boron nitride nanosheet powder in a 5M sodium hydroxide solution in a reactor, heat to 100°C and react for 24 hours, centrifuge after cooling, wash with deionized water, and dry to obtain pretreated boron nitride. Ultrasonic disperse 10g of pretreated boron nitride in 3L of deionized water, add 8g of ferric chloride, stir for 12h, then stir and dissolve 10g of 3-allyl rhodanine in 1L of 90°C hot water, add it to the reactor while stirring, stir and react for 12h, filter after cooling, wash the precipitate with ethanol, vacuum dry at 50°C for 4h, grind and sieve to obtain modified boron nitride.
[0029] Step 5. Disperse 45 g of modified white carbon black hydroxide in 300 mL of anhydrous ethanol in a reactor, disperse 10 g of modified boron nitride in 100 mL of anhydrous methanol and add sodium hydroxide to adjust the pH value to 9. Add them to the reactor under stirring, heat to 60°C and stir to react for 3 hours under nitrogen protection, filter, wash with anhydrous ethanol and deionized water, and then vacuum dry at 50°C for 4 hours to obtain a flame retardant modifier.
[0030] Step six, 20g of flame retardant modifier, 40g of natural rubber, 10g of silicone rubber, 2g of N-(4-anilinophenyl)maleimide, 3g of solid coumarone resin, 3g of sulfur and 2g of accelerator CZ are extruded through a twin-screw extruder and granulated to obtain a flexible energy storage cable material. The flexible energy storage cable material is used as a protective sheath granulate and co-extruded with a conductor and a conductor shielding layer using a non-cross-linked three-layer co-extrusion method to obtain a highly flexible energy storage cable.
[0031] In this embodiment, the process of co-extruding the flexible energy storage cable material with the conductor and the conductor shielding layer to obtain a highly flexible energy storage cable is a conventional process well known to those skilled in the art and is not limited here.
[0032] Embodiment 2: A highly flexible energy storage cable and a preparation method thereof, comprising the following steps: Step 1: Under nitrogen, 60 g of magnesium nitrate hexahydrate and 40 g of aluminum nitrate nonahydrate are dissolved in 275 mL of deionized water without carbon dioxide to obtain a salt solution. The salt solution is added dropwise to 550 mL of 1.5 M sodium nitrite solution in a reactor within 1.75 h. The addition process is magnetically stirred. During the addition process, 2 M sodium hydroxide solution is continuously added to the reactor to make the pH value of the solution 10. The temperature is raised to 65 ° C and the reaction is carried out for 32 h. After cooling, the precipitate is collected by centrifugation, and the precipitate is washed with 100 ° C deionized water and anhydrous ethanol in turn, and vacuum dried at 60 ° C for 32 h to obtain magnesium aluminum double hydroxide.
[0033] Step 2: Dissolve 72.5 g of 2-mercaptobenzimidazole in 450 mL of 1 M sodium hydroxide solution, add 45 g of zinc aluminum layered hydroxide, disperse by ultrasonication, and then stir to react for 32 h. Collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol, and dry it in vacuum at 60 ° C for 18 h to obtain modified magnesium aluminum double hydroxide.
[0034] Step 3: In a reactor, ultrasonically disperse 6.5 g of nano-silica in 325 mL of anhydrous ethanol, add 17.5 g of 3-chloropropyltriethoxysilane, heat to 50 ° C and stir for 32 h, filter and wash the precipitate with anhydrous methanol and anhydrous ethanol respectively, and vacuum dry at 50 ° C to constant weight to obtain modified nano-silica. In a reactor, disperse 6.5 g of modified nano-silica in 325 mL of anhydrous ethanol, add sodium hydroxide to adjust the pH value to 9.5, add 45 g of modified magnesium aluminum double hydroxide, heat to 50 ° C under a nitrogen atmosphere, stir and react for 27 h, filter after cooling, wash with anhydrous toluene, anhydrous ethanol and deionized water in turn, and vacuum dry at 50 ° C to obtain modified silica hydroxide.
[0035] Step 4: ultrasonically disperse the boron nitride nanosheet powder in a 5M sodium hydroxide solution in a reactor, heat to 110°C and react for 30 hours, centrifuge after cooling, wash with deionized water, and dry to obtain pretreated boron nitride. Ultrasonic disperse 12.5g of pretreated boron nitride in 3.5L deionized water, add 9g of ferric chloride, stir for 14h, then stir and dissolve 11g of 3-allyl rhodanine in 1.1L of 93°C hot water, add it to the reactor while stirring, stir and react for 14h, filter after cooling, wash the precipitate with ethanol, dry it in vacuum at 55°C for 5h, grind and sieve to obtain modified boron nitride.
[0036] Step 5. Disperse 50 g of modified white carbon black hydroxide in 325 mL of anhydrous ethanol in a reactor, disperse 12.5 g of modified boron nitride in 125 mL of anhydrous methanol and add sodium hydroxide to adjust the pH value to 9.5, add them to the reactor under stirring, heat to 65 ° C and stir to react for 3.5 hours under nitrogen protection, filter, wash with anhydrous ethanol and deionized water, and then vacuum dry at 55 ° C for 5 hours to obtain a flame retardant modifier.
[0037] Step six, 25g of flame retardant modifier, 45g of natural rubber, 12.5g of silicone rubber, 2.5g of N-(4-anilinophenyl)maleimide, 4g of liquid coumarone resin, 4g of sulfur and 2.5g of accelerator D are extruded through a twin-screw extruder and granulated to obtain a flexible energy storage cable material. The flexible energy storage cable material is used as a protective sheath granulate and co-extruded with the conductor and the conductor shielding layer using a non-cross-linked three-layer co-extrusion method to obtain a highly flexible energy storage cable.
[0038] In this embodiment, the process of co-extruding the flexible energy storage cable material with the conductor and the conductor shielding layer to obtain a highly flexible energy storage cable is a conventional process well known to those skilled in the art and is not limited here.
[0039] Embodiment 3: A highly flexible energy storage cable and a preparation method thereof, comprising the following steps: Step 1: Under nitrogen, 65 g of magnesium nitrate hexahydrate and 45 g of aluminum nitrate nonahydrate are dissolved in 300 mL of deionized water without carbon dioxide to obtain a salt solution. The salt solution is added dropwise to 600 mL of 1.5 M sodium nitrite solution in a reactor within 2 hours. The dropping process is magnetically stirred. During the dropping process, 2 M sodium hydroxide solution is continuously added to the reactor to make the pH value of the solution 10.5. The temperature is raised to 70° C. and reacted for 36 hours. After cooling, the precipitate is collected by centrifugation, and the precipitate is washed with 100° C. deionized water and anhydrous ethanol in turn, and vacuum dried at 65° C. for 36 hours to obtain magnesium aluminum double hydroxide.
[0040] Step 2: Dissolve 75 g of 2-mercaptobenzimidazole in 500 mL of 1 M sodium hydroxide solution, add 50 g of zinc aluminum layered hydroxide, disperse by ultrasound, and then stir to react for 36 h. Collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol, and dry it at 65 ° C in vacuum for 24 h to obtain modified magnesium aluminum double hydroxide.
[0041] The magnesium aluminum hydroxide is prepared by an anion exchange method, and has a layered morphology and flame retardancy. The 2-mercaptobenzimidazole is grafted into the layered structure of the magnesium aluminum hydroxide through an ion exchange reaction between the 2-mercaptobenzimidazole and the magnesium aluminum hydroxide.
[0042] Step 3: In a reactor, ultrasonically disperse 8 g of nano-silica in 350 mL of anhydrous ethanol, add 20 g of 3-chloropropyltriethoxysilane, heat to 55 ° C and stir for 36 h, filter and wash the precipitate with anhydrous methanol and anhydrous ethanol respectively, and vacuum dry at 55 ° C to constant weight to obtain modified nano-silica. In a reactor, disperse 8 g of modified nano-silica in 350 mL of anhydrous ethanol, add sodium hydroxide to adjust the pH value to 10, add 50 g of modified magnesium aluminum double hydroxide, heat to 55 ° C under a nitrogen atmosphere, stir and react for 30 h, filter after cooling, wash with anhydrous toluene, anhydrous ethanol and deionized water in turn, and vacuum dry at 55 ° C to obtain modified silica hydroxide.
[0043] After nano-silica is modified by chlorosilane coupling agent 3-chloropropyltriethoxysilane, chlorine groups exist on the surface of nano-silica, which can be grafted with 2-mercaptobenzimidazole in the modified magnesium aluminum double hydroxide to composite the nano-silica in the layered structure of the modified magnesium aluminum double hydroxide, with high composite rate and good composite strength.
[0044] Step 4: ultrasonically disperse the boron nitride nanosheet powder in a 5M sodium hydroxide solution in a reactor, heat to 120°C and react for 36 hours, centrifuge after cooling, wash with deionized water, and dry to obtain pretreated boron nitride. Ultrasonic disperse 15g of pretreated boron nitride in 4L deionized water, add 10g of ferric chloride, stir for 16h, then stir and dissolve 12g of 3-allyl rhodanine in 1.2L of 95°C hot water, add to the reactor while stirring, stir and react for 16h, filter after cooling, wash the precipitate with ethanol, vacuum dry at 60°C for 6h, grind and sieve to obtain modified boron nitride.
[0045] The boron nitride nanosheets are pretreated with sodium hydroxide, and then hydroxyl groups are grafted on the surface and reacted with iron ions to graft the iron ions on the surface of the boron nitride nanosheets. Then, 3-allyl rhodanine is used to form coordination bonds with the iron ions and initiate the polymerization of 3-allyl rhodanine, so that the 3-allyl rhodanine is coated on the surface of the boron nitride nanosheets.
[0046] Step 5. In a reactor, disperse 55 g of modified white carbon black hydroxide in 350 mL of anhydrous ethanol, disperse 15 g of modified boron nitride in 150 mL of anhydrous methanol and add sodium hydroxide to adjust the pH value to 10. Add them to the reactor under stirring, heat to 70°C under nitrogen protection, stir and react for 4 hours, filter, wash with anhydrous ethanol and deionized water, and then vacuum dry at 60°C for 6 hours to obtain a flame retardant modifier.
[0047] The 2-mercaptobenzimidazole in the white carbon black modified hydroxide undergoes an alkenyl-mercapto click reaction with the 3-allyl rhodanine on the surface of the modified boron nitride, and the modified boron nitride and the white carbon black modified hydroxide are uniformly compounded under the action of chemical bonds.
[0048] Step six, 30g of flame retardant modifier, 50g of natural rubber, 15g of silicone rubber, 3g of N-(4-anilinophenyl)maleimide, 5g of liquid nitrile rubber, 5g of sulfur and 3g of accelerator DM are extruded through a twin-screw extruder and granulated to obtain a flexible energy storage cable material. The flexible energy storage cable material is used as a protective sheath granulate and is co-extruded with the conductor and the conductor shielding layer using a non-cross-linked three-layer co-extrusion method to obtain a highly flexible energy storage cable.
[0049] In this embodiment, the process of co-extruding the flexible energy storage cable material with the conductor and the conductor shielding layer to obtain a highly flexible energy storage cable is a conventional process well known to those skilled in the art and is not limited here.
[0050] Among the flame retardant modifiers, white carbon black, magnesium aluminum double hydroxide and boron nitride all have good flame retardancy and can be used as flame retardants to fill rubber. The composite formed by them has a uniform degree of compounding and can improve the flame retardancy of rubber. Boron nitride and white carbon black have excellent thermal conductivity, which can greatly improve the thermal conductivity of cables, improve the heat dissipation capacity of cables, and weaken the thermal oxidation aging effect of cables. 3-allyl rhodanine can effectively improve the compatibility of fillers and rubber, improve the compatibility of flame retardant modifiers in rubber, and promote the dispersion of flame retardant modifiers. The well-dispersed flame retardant modifier greatly reduces the filling amount of flame retardant and filler, so that the rubber has a good degree of crosslinking during vulcanization and good thermal conductivity. The antioxidant N-(4-anilinophenyl) maleimide can also react with 2-mercaptobenzimidazole to produce a synergistic anti-aging effect. White carbon black can also reduce the penetration of oxygen in rubber and the migration of antioxidants, thereby improving the anti-aging ability of rubber.
[0051] Comparative Example 1: The difference from Example 1 is that magnesium hydroxide and aluminum hydroxide are used to replace magnesium aluminum double hydroxide.
[0052] Comparative Example 2: The difference from Example 1 is that magnesium aluminum double hydroxide is used to replace the modified magnesium aluminum double hydroxide.
[0053] Comparative Example 3: The difference from Example 1 is that a flame retardant modifier is obtained by physically mixing nano-white carbon black, magnesium hydroxide, aluminum hydroxide and silicon nitride nanosheets, and then compounded with silane coupling agent KH560 and other formula components to obtain a flexible energy storage cable material.
[0054] The sources of some reagents in the embodiments and comparative examples are as follows: 2-Mercaptobenzimidazole was purchased from MacLean Reagent Co., Ltd.
[0055] N-(4-anilinophenyl)maleimide was purchased from Wuhan Smik Biotechnology Co., Ltd.; Nano-silica was purchased from Hubei Huifu Nanomaterials Co., Ltd.
[0056] Boron nitride nanosheets are hexagonal boron nitride nanosheets purchased from Zhejiang Yamei Nanotechnology Co., Ltd.
[0057] Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, sodium nitrite, 3-allyl rhodanine, and 3-chloropropyltriethoxysilane were purchased from Sigma-Aldrich.
[0058] The flexible energy storage cable materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were vulcanized to prepare sheet samples for performance testing. The tensile strength and elongation were tested according to the standard GB / T528-2009, the flame retardant grade of the samples was tested according to the standard GB / T 10707-2008, and the thermal conductivity of the samples was tested using a thermal conductivity tester. The results are shown in Table 1: Table 1 project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 10.8 10.9 11.2 9.4 8.3 9.2 Elongation at break / % 359 364 367 335 307 321 Flame retardant grade FV-0 FV-0 FV-0 FV-1 FV-2 FV-1 Thermal conductivity W / (mK) 2.8 2.8 2.9 2.1 1.5 2.3 As can be seen from Table 1, the protective sheath granules of the flexible energy storage cable prepared by the present invention have good tensile strength and excellent elongation at break, high flexibility, high flame retardant grade, high thermal conductivity, and good thermal conductivity; Comparative Example 1 has a low degree of composite between magnesium hydroxide and aluminum hydroxide, resulting in uneven grafting with 2-mercaptobenzimidazole, and the obtained flame retardant modifier has a low degree of composite, low dispersibility in rubber, and a filler packing density higher than that of Examples 1 to 3, so the performance is poor; Comparative Example 2 is not modified with 2-mercaptobenzimidazole, so that the modified nano-white carbon black and magnesium aluminum dihydrogen oxide are not modified. The compound is only grafted in a small amount under the action of the silane coupling agent, and the obtained silica modified hydroxide has poor composite ability with modified boron nitride, and the silica modified hydroxide cannot be dispersed in the rubber matrix, and the obtained rubber has poor performance and low flame retardant grade; in Comparative Example 3, the flame retardant is physically mixed with the rubber and then compounded with the rubber under the action of the silane coupling agent. Although the silane coupling agent improves the dispersibility of the flame retardant in the rubber, the silicone hydroxyl group on the surface of silica has an adsorption effect with the vulcanization accelerator, which reduces the vulcanization speed and the crosslinking density, and the high-density filler greatly reduces the flexibility of the rubber, so the obtained rubber has poor performance.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a highly flexible energy storage cable, characterized in that: The steps include: Step 1, in a reaction kettle, disperse nano-silica in anhydrous ethanol by ultrasonic, add 3-chloropropyltriethoxysilane, heat to 45-55°C, stir for 24-36h, filter, wash the precipitate with anhydrous methanol and anhydrous ethanol respectively, and vacuum dry to constant weight to obtain modified nano-silica, disperse the modified nano-silica in anhydrous ethanol in a reaction kettle, add sodium hydroxide to adjust the pH value to 9-10, add modified magnesium aluminum double hydroxide, heat to 45-55°C under a nitrogen atmosphere, stir and react for 24-30h, filter and wash after cooling, and vacuum dry to obtain modified silica hydroxide; Step 2: In a reaction kettle, disperse the modified hydroxide of white carbon black in anhydrous ethanol, disperse the modified boron nitride in anhydrous methanol, add sodium hydroxide to adjust the pH value to 9-10, add them into the reaction kettle under stirring, heat to 60-70° C. under nitrogen protection, stir and react for 3-4 hours, filter, wash with anhydrous ethanol and deionized water, and then vacuum dry at 50-60° C. for 4-6 hours to obtain a flame retardant modifier; Step three, extrude the flame retardant modifier, natural rubber, silicone rubber, antioxidant, tackifying resin, vulcanizer and vulcanization accelerator through a twin-screw extruder and granulate to obtain a flexible energy storage cable material, and use the flexible energy storage cable material as a protective sheath granulate and a conductor and a conductor shielding layer through a non-cross-linked three-layer co-extrusion method to obtain a highly flexible energy storage cable.
2. The method for preparing a highly flexible energy storage cable according to claim 1, characterized in that: In step 1, the usage ratio of nano-white carbon black, anhydrous ethanol and 3-chloropropyltriethoxysilane is 5-8g:300-350mL:15-20g; the usage ratio of modified nano-white carbon black, anhydrous ethanol and modified magnesium aluminum double hydroxide is 5-8g:300-350mL:40-50g.
3. The method for preparing a highly flexible energy storage cable according to claim 1, characterized in that: The amount ratio of the white carbon black modified hydroxide, anhydrous ethanol, modified boron nitride and anhydrous methanol in step 2 is 45-55g:300-350mL:10-15g:100-150mL.
4. The method for preparing a highly flexible energy storage cable according to claim 2, characterized in that: The modified magnesium aluminum double hydroxide is prepared by the following steps: 2-Mercaptobenzimidazole is dissolved in 1M sodium hydroxide solution, zinc aluminum layered hydroxide is added, ultrasonic dispersion is carried out, and then stirring is carried out for 24-36 hours. The precipitate is collected by centrifugation, washed with deionized water and anhydrous ethanol, and then vacuum dried to obtain modified magnesium aluminum double hydroxide.
5. The method for preparing a highly flexible energy storage cable according to claim 4, characterized in that: The usage ratio of the 2-mercaptobenzimidazole, the sodium hydroxide solution and the zinc-aluminum layered hydroxide is 70-75 g: 400-500 mL: 40-50 g.
6. The method for preparing a highly flexible energy storage cable according to claim 5, characterized in that: The zinc-aluminum layered hydroxide is prepared by the following steps: Under nitrogen flow, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in deionized water without carbon dioxide to obtain a salt solution, and the salt solution is added dropwise to a 1.5M sodium nitrite solution in a reaction kettle within 1.5-2 hours, and magnetic stirring is performed during the dropping process. 2M sodium hydroxide solution is continuously added to the reaction kettle during the dropping process to make the pH value of the solution 9.5-10.5, and the temperature is raised to 60-70°C for reaction for 24-36 hours. After cooling, the mixture is centrifuged, washed, and vacuum dried to obtain magnesium aluminum double hydroxide.
7. The method for preparing a highly flexible energy storage cable according to claim 6, characterized in that: The dosage ratio of the magnesium nitrate hexahydrate, the aluminum nitrate nonahydrate, the deionized water and the sodium nitrite solution is 50-65 g: 30-45 g: 250-300 mL: 500-600 mL.
8. The method for preparing a highly flexible energy storage cable according to claim 1, characterized in that: The modified boron nitride described in step 2 is prepared by the following steps: In a reaction kettle, the boron nitride nanosheet powder is ultrasonically dispersed in a 5M sodium hydroxide solution, heated to 100-120°C for reaction for 24-36 hours, cooled, centrifuged, washed with deionized water, and dried to obtain pretreated boron nitride, the pretreated boron nitride is ultrasonically dispersed in deionized water, ferric chloride is added, and stirred for 12-16 hours, and then 3-allyl rhodanine is stirred and dissolved in hot water at 90-95°C, added to the reaction kettle while stirring, stirred for reaction for 12-16 hours, cooled, filtered, the precipitate is washed with ethanol, vacuum dried at 50-60°C for 4-6 hours, and ground and sieved to obtain modified boron nitride.
9. The method for preparing a highly flexible energy storage cable according to claim 8, characterized in that: The dosage ratio of the pretreated boron nitride, deionized water, ferric chloride, 3-allyl rhodanine and hot water is 10-15 g: 3-4 L: 8-10 g: 10-12 g: 1-1.2 L.
10. A highly flexible energy storage cable, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of flexible cable sheath material
CN106977778A
Environment-friendly flame-retardant rubber and preparation method thereof
CN118620388A
Epoxy resin for motor encapsulation and preparation method thereof
CN118978792A
Cabtire cable, insulated electric wire for cabtire cable and method for manufacturing them
JP2020161447A